Pt. Thiyagaraya Chettiyar: A Cooperative Pioneer in Indian Banking and Finance - Premalatha, Mrs. G.; Mary, Sr. S. Emelda (Journal of Neonatal Surgery, 2025)
This research also evaluates the inputs of Mr. Pt.Thiyagaraya Chettiyar for his contribution towards the development of cooperative banking and finance in India and for his contributions shown in the spread of financial education, institution of cooperative lending schemes and successful formulation of policies and other executes leading to the human and socio-economic progress of the country. The research methodology used is a dual design type: descriptive and analytical. In so doing, this design methodology makes a systematic descriptive design capture of Pt. Thiyagaraya Chettiyar’s contributions to cooperative banking and financial development, while the analytical design explores the connections between social and economic consequences of his works in finance, particularly for excluded groups. The sample comprises 71 respondents who have been chosen randomly using a structured questionnaire that contains data from Cooperative Bank members and Financial Experts, Government Policymakers, and Academicians. The datasets were obtained through a set of identifiable questionnaires which included both close-ended questions and scale questions and the data were analyzed using the SPSS software. Other Statistical tests for inferences includes One-Way ANOVA, Independent Sample t-Test and Fried-man Test. It has been ascertained from the analysis that Pt. Thiyagaraya Chettiyar claims that the above contributions “I made can go a long way in improving great access to credit, financial literacy and socio-economic empowerment of women and the lower castes who suffered from false stigma”. He was the scrupulous force in the creation of Cooperative Banks since it offer independence to the rural and agrarian communities. The study therefore explores how his work is still relevant in the current cooperative banking and policies such as the question of social inclusion and fair credit. Pt. Thiyagaraya Chettiyar has provided a model for reforming and creating modern sustainable peace, today’s reform processes are forcibly distinguished by the example left by Chettiyar. The principles expounded by the author argue well to the existing issues in cooperative banking and financial evolution.